(untitled) (Bangladesh Journal of Agriculture, 2022)
A field experiment was carried out at Tuber Crops Research Sub Center, Seujgari, Bogura, Bangladesh to assess the effect of plant growth regulators on tomato during the winter season of 2020-2021. Four Plant Growth Regulators (PGRs) available in market viz., PGR1 = Flora @ 20 ppm, PGR2= Protozim @ 20 ppm, PGR3= Vagimax and PGR4= Miraculan@ 20 ppm were used, and there was a control no use of PGR was used as control in the study. The experiment was conducted in RCBD with three replications. The growth and yield contributing characters significantly differed due to plant growth regulators. The maximum number of fruits/plant (65) was recorded from PGR treatment (application of Flora @ 20 ppm) while the minimum number of fruits/plant (25) was recorded from the control treatment (no application of plant growth regulators). Plant growth regulators had significant influence on growth and yield of tomato. The highest yield (36.21 t/ha) and highest Photosynthesis (Chlorophyll a, Chlorophyll b and Total Chlorophyll) was obtained from the application of PGR1 = Flora @ 20 ppm plant growth regulator. The maximum Benefit Cost Ratio (BCR) (3.34) was also recorded from PGR1 treatment, while the minimum BCR (1.66) was recorded from control (no application of plant growth regulators). Among the four PGRs i.e., application of Flora @ 20 ppm showed the best result in tomato production. Bangladesh J. Agri. 2019-2021, 44-46: 141-146